2015
DOI: 10.1080/20786190.2015.1024013
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional profile and outcome assessment of adult patients triaged away from Steve Biko Academic Hospital emergency unit

Abstract: Background:Overcrowding is a global problem in emergency medicine. This study examined an approach to this problem at a central hospital. Methods: A prospective observational study was done to provide a cross-sectional profile of patients triaged away from the emergency unit (EU) and to evaluate their outcome by telephonic survey. Results: 549 patients were triaged away during the study period. There was no significant difference in the number of male and female patients in the sample. Female patients were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The effective utilisation of triage could direct patients immediately to the appropriate health care professional (Harding et al 2011;Rhoda et al 2010). Implementing a triage system in PHC facilities therefore could decrease waiting times and improve the accessibility and quality of care (Engelbrecht, Du Toit & Geyser 2015;Finamore & Turris 2009). The literature study indicated that there was a correlation between patients' waiting times at health facilities and patients' satisfaction levels (Blitz et al 2008).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective utilisation of triage could direct patients immediately to the appropriate health care professional (Harding et al 2011;Rhoda et al 2010). Implementing a triage system in PHC facilities therefore could decrease waiting times and improve the accessibility and quality of care (Engelbrecht, Du Toit & Geyser 2015;Finamore & Turris 2009). The literature study indicated that there was a correlation between patients' waiting times at health facilities and patients' satisfaction levels (Blitz et al 2008).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…Internationally and nationally, different triage systems are implemented in emergency departments, both in private and in public hospitals, with good results (Blitz et al 2008). According to Engelbrecht et al (2015), overcrowding of patients with minor ailments in emergency departments occurred because PHC facilities are overcrowded with patients suffering from various conditions. In South Africa, no scientific reports could be found about the implementation of triage in PHC facilities.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…In the study conducted in Cape Town public EDs, health care providers described limited bed availability, staff shortage and high rate of boarders in the ED as outcomes of crowding which lead to prolonged ED LOS [ 27 ]. The ED of the study hospital is often understaffed and overburdened as in the case of many similar hospitals in South Africa [ 28 ]. The 2014 statistics revealed continuous challenges relating to patients' LOS in the ED – for example, patient remained in the ED for up to 5 days [ 28 ] - despite aiming for patients to be transferred form the ED within at least 12-h (informal communication by the head of department).…”
Section: Introductionmentioning
confidence: 99%
“…The ED of the study hospital is often understaffed and overburdened as in the case of many similar hospitals in South Africa [ 28 ]. The 2014 statistics revealed continuous challenges relating to patients' LOS in the ED – for example, patient remained in the ED for up to 5 days [ 28 ] - despite aiming for patients to be transferred form the ED within at least 12-h (informal communication by the head of department). The exact cause of prolonged LOS in the study ED was unknown as measuring waiting times were not routine practice.…”
Section: Introductionmentioning
confidence: 99%